Premonstratensian Settlement in the Czech Lands and Ireland, 1142-1250 - Clyne, Miriam (Journal of Medieval Monastic Studies, 2018)
Abstract The settlement of Premonstratensian canons and nuns is addressed against the backdrop of the political and ecclesiastical settings of the Czech Lands and Ireland. Colonization was accomplished through political alliances, religious circles, and interaction with the central authority at Prémontré during transitional phases of diocesan reform in Bohemia, Moravia, and Connacht, and Anglo-Norman acculturation in Ulster. The letters of the father abbot at Steinfeld and the abbots of Prémontré indicate their concerns for the future prospects of the distant monasteries, the needs of new communities, and how they reacted in different ways to maintain standards of uniformity and discipline.